Profil Peresepan Fall Risk Medicine pada Pasien Lanjut Usia di Rumah Sakit Islam Jakarta Cempaka Putih: Prescribing Profile of Fall Risk Medicines for Geriatric Patients at Islam Cempaka Putih Hospital in Jakarta - Fadillah, Aditya Nur; Safrina, Ulya; Nida, Khairun; Fajri, Purnama; Kurniawan, Adin Hakim (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
In general, older adults will experience physical and psychological changes, which can cause physical problems, such as falls. Another cause that increases the risk of falls in the elderly is using fall-risk medication (FRM). Elderly people who take >5 types of medication (polypharmacy) have a greater chance of falls. This study aimed to determine the profile of drug use that can potentially cause falls in the elderly. This study used a retrospective design. Data was collected at the Outpatient Installation of the Cempaka Putih Islamic Hospital. The sampling technique used was convenience sampling. The samples studied were 107 patients. Data comes from patient medical records and medication history at the Pharmacy Installation in October-December 2022. 91 patients (85.05%) of 107 used fall-risk medication (FRM). Respondents were dominated by women (52.34%) in the age category 60-74 years (elderly). The majority of patients did not have comorbidities (53.85%). The drugs frequently prescribed are cardiovascular drugs (71.96%), namely antihypertensives (66.36%). 71 patients (66.36%) used FRM, included in the low-risk category, and as many as 20 patients (18.69%) used FRM in the high-risk category. 27 patients were still using FRM ?6 drugs (25.23%). The use of FRM is still relatively high, and it is necessary to evaluate the risks and benefits of its use to prevent falls. Keywords: Fall, Fall risk medicine, elderly Abstrak Lanjut usia secara umum akan mengalami perubahan kondisi fisik dan psikis, sehingga dapat menyebabkan masalah fisik, seperti jatuh. Penyebab lain yang meningkatkan resiko jatuh pada lansia adalah penggunaan fall risk medicines (FRM). Lansia yang mengonsumsi >5 jenis obat (polifarmasi) memiliki resiko jatuh lebih besar. Tujuan penelitian ini adalah untuk mengetahui profil penggunaan obat yang berpotensi menyebabkan jatuh (fall risk medicines) pada lansia. Penelitian ini menggunakan rancangan design retrospektif. Pengambilan data dilakukan di Instalasi Rawat Jalan Rumah Sakit Islam Cempaka Putih. Teknik sampling yang digunakan adalah convenience sampling. Sampel yang diteliti sebanyak 107 pasien. Data bersumber dari rekam medis pasien dan dari riwayat pengambilan obat di Instalasi Farmasi pada bulan Oktober-Desember Tahun 2022. Terdapat 91 pasien (85,05%) dari 107 pasien yang menggunakan fall risk medicines (FRM). Responden didominasi oleh perempuan (52,34%) dengan kategori usia 60-74 tahun (elderly). Mayoritas pasien tidak memiliki komorbid (53,85%). Golongan obat yang sering diresepkan adalah obat kardiovaskular (71,96%), yaitu antihipertensi (66,36%). Sejumlah 71 pasien (66,36%) menggunakan FRM yang termasuk dalam kategori risiko rendah dan sebanyak 20 pasien (18,69%) menggunakan FRM dalam risiko tinggi. 27 pasien masih menggunakan FRM ?6 obat (25,23%). Penggunaan FRM yang masih cukup tinggi perlu dievaluasi resiko dan manfaat penggunaannya untuk mencegah kejadian jatuh. Kata Kunci: Jatuh, fall risk medicine, lansia